Budaya Mutu Layanan Madrasah Aliyah Negeri Se-Kota Kediri Ditinjau dari Kepemimpinan Profetik dan Kinerja Tenaga Kependidikan - Moh Hanif Adzhar; Diki Darmawan; Muhamad Yasin (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the influence of prophetic leadership and the performance of education personnel on the culture of quality education services in the State Aliyah Madrasah (MAN) in Kediri City. Through associative quantitative methods, data were obtained from 53 education personnel using saturation sampling techniques and analyzed with multiple regression assisted by SPSS 27 to test the partial and simultaneous effects of independent variables on quality culture. The results showed that prophetic leadership had a significant effect on service quality culture with a t value = 3.560, sig. = 0.001, and regression coefficient (B) = 0.612. This shows that an increase in prophetic leadership consistently has a strong impact on quality culture through exemplary, motivational, and moral reinforcement. The performance of education personnel has a significant effect with a t value = 2.281, sig. = 0.026, and regression coefficient (B) = 0.495, which means that improving the performance of education personnel significantly contributes to the creation of more orderly, responsive, and productive services. Simultaneously, the two variables contributed 50.7% to the culture of service quality, while 49.3% was influenced by other factors outside this study. The findings confirm that prophetic leadership and the performance of education personnel are strategic factors in strengthening the culture of quality education services.